The Role of the ECM in Lung Cancer Dormancy and Outgrowth - Parker, Amelia L.; Cox, Thomas R. (Frontiers in Oncology, 2020)
The dissemination of tumour cells to local and distant sites presents a significant challenge in the clinical management of many solid tumours. These cells may remain dormant for months or years before overt metastases are re-awakened. The components of the extracellular matrix, their posttranslational modifications and their associated factors provide mechanical, physical and chemical cues to these disseminated tumour cells. These cues regulate the proliferative and survival capacity of these cells and lay the foundation for their engraftment and overt colonisation. Crosstalk between tumour cells, stromal and immune cells within primary and secondary sites is fundamental to extracellular matrix remodelling that feeds back to regulate tumour cell dormancy and outgrowth. This review will examine the role of the extracellular matrix and its associated factors in establishing a fertile soil from which individual tumour cells and micrometastases establish primary and secondary tumours. We will focus on the role of the lung extracellular matrix in providing the architectural support for local metastases in lung cancer, and distant metastases in many solid tumours. This review will define how the matrix and matrix associated components are collectively regulated by lung epithelial cells, fibroblasts and resident immune cells to orchestrate tumour dormancy and outgrowth in the lung. Recent advances in targeting these lung-resident tumour cell subpopulations to prevent metastatic disease will be discussed. The development of novel matrix-targeted strategies has the potential to significantly reduce the burden of metastatic disease in lung and other solid tumours and significantly improve patient outcome in these diseases.